FERTILITY VARIATION OF Melaleuca cajuputi subsp. cajuputi AND ITS IMPLICATION IN SEED ORCHARD MANAGEMENT - Kartikawati, Noor K. (Association of Indonesian Forestry and Environment Researchers and Technicians, 2016)
Information about fertility variation of flowering trees in seed orchard including determining the quality of seed production and estimating the genetic diversity are still lacking. This paper evaluates fertility variation, effective population size and genetic diversity among cajuput trees in seedling seed orchard at Paliyan, Gunungkidul for optimizing seed orchard management. A total of 160 trees were observed in three flowering periods of 2011-2013. The fertility based on the number of flowers and fruits were registered for each tree at the age of 12, 13 and 14 years. Results show that there are similar patterns of fertility after three years observation. Sibling coefficients (Ψ) which show fertility variation during three flowering periods are 1.39, 1.25 and 1.43 respectively. They show deviation from random mating, because of individual imbalance for producing flowers and fruits. However, the number of fertile trees was comparatively higher at 2011. More than 15 families of effective population size were recorded each year and supported more than 75% individuals in seed orchard to contribute flowers and seeds. High value of genetic diversity was calculated based on fertility variation (0.965, 0.967 and 0.957, respectively). Fertility variation led to consequence on seed deployment, including seeds of fertile families which should be collected equally and mixed to compose equal proportion of seeds and to avoid domination of highly fertility families and genetic drift. Silvicultural treatments in seed orchard management were indispensable to promote fertility uniformity and to increase effective population size in seed orchard for obtaining maximal genetic gain.